2022
DOI: 10.1111/bcpt.13706
|View full text |Cite
|
Sign up to set email alerts
|

Describing long‐term opioid use utilizing Nordic prescription registers—A Norwegian example

Abstract: Previous studies have de ned long-term opioid use in varying ways, decreasing comparability, reproducibility and clinical applicability of the research. Based on recent systematic reviews, we aimed to estimate long-term opioid use de ned as use persisting more than three months using one of the Nordic prescription registers. We used the Norwegian Prescription Register (NorPD) to extract data on all opioid dispensations between January 1st 2004 and October 31st 2019. New users of opioids (washout 365 days) were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The count measure for each developmental stage was chosen based on the knowledge that prescription opioid use is relatively rare among adolescents and young adults and that very few will meet the criteria of previously used definitions for persistent use. 32 , 33 Prescriptions with a reimbursement code indicating palliative care (−90) were excluded. 48 , 49…”
Section: Methodsmentioning
confidence: 99%
“…The count measure for each developmental stage was chosen based on the knowledge that prescription opioid use is relatively rare among adolescents and young adults and that very few will meet the criteria of previously used definitions for persistent use. 32 , 33 Prescriptions with a reimbursement code indicating palliative care (−90) were excluded. 48 , 49…”
Section: Methodsmentioning
confidence: 99%
“…Incident opioid use was defined by a washout period of 365 days, during which no opioid dispensations were allowed. See Hamina et al 24 for a detailed explanation of the cohort formation methods.…”
Section: Methodsmentioning
confidence: 99%
“…Utilising the methodology for defining long-term opioid use described in this article, Hamina et al found that one in seven persons who were dispensed opioids used them longer than three months at some time point during 2004–2019, with little change in the prevalence and incidence of long-term opioid use during the follow-up. 24 The work to identify risk factors for becoming a long-term opioid user and the consequences of long-term opioid use will continue throughout the coming years.…”
Section: Findings To Date and Future Plansmentioning
confidence: 99%
“…For instance, from 2000 to 2017, the prevalence of CNCP in Denmark increased from 19.5% to 27.8% (Ekholm et al, 2022). This is a serious public health issue particularly when associated with indiscriminate use of prescribed opioids (Birke et al, 2016; Hamina et al, 2022; Ju et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to an estimate based on recent growth in opioid consumption in Norway, approximately 14% of all new opioid users progress to long‐term use (Hamina et al, 2022), which is concerning given the limited evidence of efficacy of long‐term opioid treatment (L‐TOT) for chronic non‐cancer pain (Busse et al, 2018; Currow et al, 2016; Krebs et al, 2018; Sehgal et al, 2013) and the numerous opioid‐related adverse events that have been reported in this population (Els et al, 2017).…”
Section: Introductionmentioning
confidence: 99%